Operando Observations of Reversible α-BiF3 Conversion in Liquid Electrolyte by Synchrotron Radiation Diffraction and 7Li Nuclear Magnetic Resonance. Issue 12 (17th August 2020) - Kawasaki, Mitsuo; Kiuchi, Hisao; Shimoda, Keiji; Kano, Gentaro; Fujimoto, Hiroyuki; Ogumi, Zempachi; Abe, Takeshi
Abstract : The electrochemically-driven conversion reaction of BiF3 with Li + ions is of interest for potential application as a positive electrode system in conversion type rechargeable batteries. Here, we use synchrotron radiation diffraction and 7 Li nuclear magnetic resonance (NMR) for complementary operando observations of reversible or quasi-reversible conversion reactions of α -BiF3 nanocomposite electrode at room temperature. The nanocomposite electrode was fabricated by ball milling and subsequent heat treatments. A pronounced XRD peak broadening indicated a disordered fine crystalline state in the electrode. The operando synchrotron radiation diffraction measurements revealed a quasi-reversible smooth crystallographic transformation between α -BiF3 and metallic Bi. The operando 7 Li NMR measurement quantitatively showed reversible conversion reactions. The series of in-situ 7 Li NMR spectra contained sharp signals from Li + ions in the electrolyte and a broad signal associated with a solid phase of LiF. These signals followed a stoichiometric relationship that conformed to a three-electron BiF3 conversion pathway.